Proposing a quantitative index to measure the industrialisation level of building projects - Sotorrío Ortega, Guillermo; Cobo Escamilla, Alfonso; Tenorio Ríos, José A. (Results in engineering, 2025)
•New dynamic method to measure industrialisation in construction.•Integrates factory-work ratio, cost relevance, and sustainability impact.•Adapts to any project context, overcoming static models.•Enhances strategic decisions in both new builds and retrofits.•Links industrialisation to real sustainability outcomes. The industrialisation of construction has been the subject of numerous studies that aim to enhance efficiency, sustainability and quality in this sector. The existing systems for measuring the level of industrialisation in building projects involve qualitative approaches such as classifications by levels, or quantitative ones based on cost sharing. These models, however, are usually static and do not take into consideration the influence of each work unit within the project, which reduces its applicability in specific contexts. This study develops a quantitative and adaptable methodology for evaluating an industrialisation level index in construction projects, taking into account key factors such as the proportion of the work completed in the factory and on site, the economic importance of each work unit and its contribution to the overall sustainability of the project. The proposed model makes it possible to distinguish the true impact of industrialisation more accurately, avoiding the limitations of generalised approaches. The methodology enables industrialised solutions to be integrated more accurately into rehabilitation projects and new builds, providing an objective tool for strategic decision-making in construction. The system proposed improves on the existing models by offering a dynamic and adaptable evaluation, adjusting the industrialisation rate of each work unit according to its importance within the project. The methodology represents a significant improvement in the measurement of industrialisation in construction, providing a more accurate reference framework for optimising building processes. The Industrialisation Level Index (ILI) ranged from 0.05 to 0.80 across 14 test cases, demonstrating its ability to capture a wide variety of industrialisation levels. The tool supports strategic decisions in selecting industrialised construction systems for cost and time efficiency.